Perindopril Improves Cardiac Function by Enhancing the Expression of SIRT3 and PGC-1α in a Rat Model of Isoproterenol-Induced Cardiomyopathy - Zhu, Zhenyu; Li, Huihui; Chen, Wanli; Cui, Yameng; Huang, Anan; Qi, Xin (Frontiers in Pharmacology, 2020)
Mitochondrial biosynthesis regulated by the PGC-1α-NRF1-TFAM pathway is considered a novel potential therapeutic target to treat heart failure (HF). Perindopril (PER) is an angiotensin-converting enzyme inhibitor that has proven efficacy in the prevention of HF; however, its mechanism is not well established. In this study, to investigate the mechanisms of PER in cardiac protection, a rat model of cardiomyopathy was established by continuous isoproterenol (ISO) stimulation. Changes in the body weight, heart weight index, echocardiography, histological staining and biochemical indicators were examined. Our results demonstrate that PER reduced myocardial remodeling, inhibited deterioration of cardiac function, and delayed HF onset in rats with ISO-induced cardiomyopathy. PER markedly reduced reactive oxygen species (ROS) production, increased the levels of antioxidant enzymes, improved the function of the mitochondrial respiratory chain, and promoted ATP production in myocardial tissues. In addition, PER inhibited cytochrome C release in mitochondria and caspase-3 activation in the cytosol, thereby reducing the apoptosis of myocardial cells. Notably, PER remarkably up-regulated the mRNA and protein expression levels of Sirtuin 3 (SIRT3), peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α), nuclear respiratory factor 1 (NRF1) and mitochondrial transcription factor A (TFAM) in myocardial cells. Collectively, our results suggest that PER induces mitochondrial biosynthesis-mediated enhancement of SIRT3 and PGC-1α expression, thereby improving the cardiac function in rats with ISO-induced cardiomyopathy.